1990
DOI: 10.1016/0735-1097(90)90346-q
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of “silent” restenosis and long-term follow-up after successful angioplasty in single vessel coronary artery disease: The value of quantitative exercise electrocardiography and quantitative coronary angiography

Abstract: Exercise electrocardiographic (ECG) testing during follow-up after coronary angioplasty is widely applied to evaluate the efficacy of angioplasty, even in asymptomatic patients. One hundred forty-one asymptomatic patients without previous myocardial infarction underwent quantitative exercise ECG testing and quantitative coronary angiography 1 to 6 months after successful angioplasty in single vessel coronary artery disease to 1) determine the value of exercise ECG testing to detect "silent" restenosis, and 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…We followed up the patients with BMS 9.8±9.3 months. A pooled analysis of 15 treadmill studies involving 2250 patients with angiographic follow-up showed a 50% positive predictive value and a 76% negative predictive value for the exercise treadmill test [37][38][39][40][41]. Therefore, the higher stent restenosis rate may be related to the longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…We followed up the patients with BMS 9.8±9.3 months. A pooled analysis of 15 treadmill studies involving 2250 patients with angiographic follow-up showed a 50% positive predictive value and a 76% negative predictive value for the exercise treadmill test [37][38][39][40][41]. Therefore, the higher stent restenosis rate may be related to the longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of exercise stress tests increases with the extent of coro nary artery disease, which implies a low sensi tivity in those patients with only single-vessel disease [2,5,6], Although some investigators [7] report a good correlation between symp toms and angiographic restenosis, others [8] (including ourselves) failed to do so.…”
Section: Comparison With Other Studiesmentioning
confidence: 97%
“…According to our results, incorporation of right-sided chest leads improved the reliability of the technique (Se, Sp, Ppv, Npv, and Ac up to 79%, 97%, 69%, 98%, and 95% respectively) in levels similar or even better to them from SPECT and stress echocardiography. 10,11,18,19 The improvement in the ability of exercise testing in detecting coronary artery disease and restenosis in RCA and LCX with the use of right-sided chest leads seems reasonable since V 3 R through V 5 R leads (which are located symmetrically to V 3 R through V 5 R in the right hemithorax) ''view'' the inferolateral surface of the heart which is dominantly supplied from RCA and LCX.…”
Section: Discussionmentioning
confidence: 99%